Processos estocásticos de reação e difusão na rede e cadeias quânticas - Mendonça, José Ricardo Gonçalves de (2000)
In this work we investigate some reaction-difusion stochastic processes on the lattice. In particular, we determine the universality classes of critical behavior of a nonequilibrium surface growth process and of the basic contact process. Our main tools of investigation are exact numerical diagonalizations and finite-size scaling ideas. We also present an application of the Bethe ansatz in the exact diagonalization of the infinitesimal generator of a di_usion process of particles without exclusion known as the zero range process.